Merriam-webster's elementary dictionary (Merriam-Webster, 2019)
This newly revised dictionary for young students cover the vocabullary needed today, including many words from the fields of science and technology. More than 36,000 entries with expanded definitions, usage examples, and nearly 1,300 quotes from classic and contemporary children's literature.